Law Enforcement Against Rohingya Refugees Involved in Criminal Activities in Medan City - Muhammad Ryan Eka Ramadhan; Fitria Ramadhani Siregar (CERED Indonesia Institute, 2025)
Rohingya is one of the Islamic ethnic minorities and is isolated in the country of Myanmar. The Rohingya ethnic group has been in the Rakhine Region for a long time, even before the British came to power between 1824 and 1948. However, the existence of the Rohingya ethnic group was not recognized by the Myanmar Military Junta government so that throughout their survival the Rohingya ethnic group was not strong enough to face violence committed by the government. In the end, the Rohingya were forced to travel to other countries, including Indonesia, by boat. Indonesia is one of the countries that is a destination for refugees due to discrimination or conflict in their country. Rohingya refugees who temporarily stop in Indonesia is a humanitarian problem and the country must respond to this matter as best as possible. However, before 2016, Indonesia did not have a regulation to regulate the refugee problem because Indonesia did not participate in ratifying the 1951 Refugee Convention. Regarding the presence of foreigners, including Rohingya refugees, in 2016, the Indonesian Government issued regulations to address the refugee problem, namely through Presidential Regulation of the Republic of Indonesia Number 125 of 2016 concerning Handling of Refugees from Abroad. This regulation regulates the handling of refugees which includes aspects of discovery, security, shelter, supervision, international cooperation and various other aspects including handling refugees who are involved in criminal activities. Therefore, the author formulates problems related to law enforcement against Rohingya refugees who are involved in criminal activities